Targeted Coagulation Management in Severe Trauma: The Controversies and the Evidence. (October 2016) - Winearls, James; Reade, Michael; Miles, Helen; Bulmer, Andrew; Campbell, Don; Görlinger, Klaus; Fraser, John F.
Abstract : Hemorrhage in the setting of severe trauma is a leading cause of death worldwide. The pathophysiology of hemorrhage and coagulopathy in severe trauma is complex and remains poorly understood. Most clinicians currently treating trauma patients acknowledge the presence of a coagulopathy unique to trauma patients—trauma-induced coagulopathy (TIC)—independently associated with increased mortality. The complexity and incomplete understanding of TIC has resulted in significant controversy regarding optimum management. Although the majority of trauma centers utilize fixed-ratio massive transfusion protocols in severe traumatic hemorrhage, a widely accepted "ideal" transfusion ratio of blood to blood products remains elusive. The recent use of viscoelastic hemostatic assays (VHAs) to guide blood product replacement has further provoked debate as to the optimum transfusion strategy. The use of VHA to quantify the functional contributions of individual components of the coagulation system may permit targeted treatment of TIC but remains controversial and is unlikely to demonstrate a mortality benefit in light of the heterogeneity of the trauma population. Thus, VHA-guided algorithms as an alternative to fixed product ratios in trauma are not universally accepted, and a hybrid strategy starting with fixed-ratio transfusion and incorporating VHA data as they become available is favored by some institutions. We review the current evidence for the management of coagulopathy in trauma, the rationale behind the use of targeted and fixed-ratio approaches and explore future directions.